Development of a scalable mental healthcare plan for a rural district in Ethiopia. (January 2016) - Fekadu, Abebaw; Hanlon, Charlotte; Medhin, Girmay; Alem, Atalay; Selamu, Medhin; Giorgis, Tedla W.; Shibre, Teshome; Teferra, Solomon; Tegegn, Teketel; Breuer, Erica; Patel, Vikram; Tomlinson, Mark; et al.
Abstract : Background: Developing evidence for the implementation and scaling up of mental healthcare in low- and middle-income countries (LMIC) like Ethiopia is an urgent priority. Aims: To outline a mental healthcare plan (MHCP), as a scalable template for the implementation of mental healthcare in rural Ethiopia. Method: A mixed methods approach was used to develop the MHCP for the three levels of the district health system (community, health facility and healthcare organisation). Results: The community packages were community case detection, community reintegration and community inclusion. The facility packages included capacity building, decision support and staff well-being. Organisational packages were programme management, supervision and sustainability. Conclusions: The MHCP focused on improving demand and access at the community level, inclusive care at the facility level and sustainability at the organisation level. The MHCP represented an essential framework for the provision of integrated care and may be a useful template for similar LMIC.